IT Management in the Digital Society - ANDREICA, Alina Bianca (2023)
Cumpărați cartea în format tipărit.Digitalization is now one of the leading global trends. Digitalization penetrates and changes all aspects of society: science, technology, industry, social media, and societal systems. The first edition of the book by Alina Andreica on the management of digital systems, which appeared in 2009, was visionary because it anticipated the role digital systems will play in the future. The second edition of the book is, in fact, much more than just a second edition.The chapters that have been added cover new and critical topics: Web 2.0 and the social impact of digitalization … and formulate practical tasks for practicing the tools and approaches covered in the book chapters. In the extended Chapter 9, the information systems implemented at BBU are discussed in detail as best practice examples. Also, all over the book highly relevant information on EU statistics and digital indicators about digital systems is provided.The new edition of the book is an excellent contribution to the development of digital transformation and is highly relevant not only for academia but for all areas of society.Bruno BuchbergerProfessor of Computer MathematicsResearch Institute for Symbolic ComputationJohannes Kepler University, Linz – Hagenberg, Austria